A Protection of Indonesian Citizens by the Indonesian Consulate General in Jeddah Through Consular Functions Under the 1963 Vienna Convention: 2017 Bomb Joke Case - Shalsabila Aurelia; Mansur Juned (TRANSBORDERS: International Relations Journal, 2026)
Protection of nationals abroad constitutes a fundamental consular function regulated under the Vienna Convention on Consular Relations 1963 (VCCR 1963) and represents a key pillar of contemporary consular diplomacy. This article analyzes the implementation of consular functions by the Consulate General of the Republic of Indonesia (KJRI) in Jeddah in providing consular protection to Indonesian nationals involved in a bomb joke incident at King Abdulaziz International Airport in 2017, based on Articles 5 and 36 of VCCR 1963. Employing a qualitative single-case study approach based on in-depth interviews and document analysis, the study reveals that KJRI Jeddah effectively implemented its consular duties through prompt emergency response by the Citizen Protection Task Force, legal assistance, provision of a retainer lawyer and interpreters, consular visitations, and repatriation facilitation. Overall, these actions were consistent with Articles 5 and 36 of VCCR 1963. However, the effectiveness of consular diplomacy faced structural limitations, including the rigid nature of Saudi Arabian criminal law, restricted initial consular access during early investigation in Riyadh, and the absence of a bilateral Mandatory Consular Notification (MCN) agreement between Indonesia and Saudi Arabia.